Time required to protect the intestinal tract of chicks against Salmonella enterica serovar enteritidis using competitive exclusion - Sterzo, Ev [UNESP] (2005)
Competitive exclusion (CE) has been designed to accelerate the colonization of the alimentary tract of young commercial birds and it has been also used to repopulate the digestive tract after antibiotic therapy. The method has been successfully adopted as a means to prevent enteric salmonellosis. The present study was carried out to evaluate if CE is able to prevent this kind of infection. Newly hatched chicks were given a CE culture and at different intervals of time birds infected with Salmonella Enteritidis were placed together with the group of treated birds. CE culture was prepared from feces of adult laying hens incubated overnight at 37C under aerobic conditions. Birds were killed 4 and 8 days after challenge and viable counts of Salmonella Enteritidis were assessed in the cecal contents. The results showed that Salmonella infection was reduced even if CE culture administration was concomitant with the inclusion of the infected bird in the group.